UPAYA PENGURUS KOPERASI UNTUK MENINGKATKAN PARTISIPASI ANGGOTA KOPERASI SERBA USAHA MITRA SAKINAH PONTIANAK - Azis, Muhamad Abdul; Khosmas, F.Y; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the efforts of cooperative management to increase member participation and the level of member participation in the Sakinah Mitra Multipurpose Cooperative Pontianak. This research method is descriptive method with a qualitative approach. This research uses data collection techniques direct communication with data collection tools in the form of interview guidelines and documentary studies in the form of note sheets. The results of this study indicate that the efforts of the Pontianak Sakinah Mitra Multipurpose Cooperative management undertake two indicators. The following conclusions specifically from the efforts of cooperative management to increase member participation in the Sakinah Mitra Multipurpose Cooperative Pontianak: 1) the efforts made were quite successful using a material approach by giving bonuses in the form of home furnishings to active members and non-material approaches in the form of motivation and management actively involving members in all components of involvement in business planning and decision making 2) the level of member participation in the presence of quite active member meetings, capital contributions, service utilization, and supervision by members.Keywords: Cooperative Management Efforts, Member Participation